Validity and reliability of a futsal performance test based on multiple intelligences - Yanto, Anggel Hardi; Ilham; Ali, Muhammad; Palmizal (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to develop a futsal performance test instrument based on the theory of multiple intelligences for futsal athletes, and to assess its feasibility and effectiveness. The research used the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation phases. The sample consisted of students enrolled in the Sports Coaching Education Study Program at the University of Jambi who were registered in the futsal course. Two trial groups were involved: a limited-scale trial with 30 students and a large-scale trial with 90 students, selected through simple random sampling. Sampling criteria were based on enrollment in the futsal course, as per the curriculum of the Sports Coaching Education (PORKES) Study Program. Data collection techniques included questionnaires and performance tests. Analysis methods involved content validity testing (Aiken’s V), construct validity testing (Confirmatory Factor Analysis), and product effectiveness evaluation using descriptive statistics. The development process produced an instrument consisting of 18 components, each with a factor loading above 0.3, indicating strong construct validity. Content validity, assessed by three experts using the Delphi method, yielded a total Aiken’s V value of 1.141. The reliability coefficient was 0.807, indicating high internal consistency. These results demonstrate that the developed futsal test instrument is both valid and reliable for evaluating futsal performance based on multiple intelligences.